Suffrage, Labour Markets and Coalitions in Colonial Virginia - Elena Nikolova; Milena Nikolova (Institute for the Study of Labor (IZA), 2016)
We study Virginia's suffrage from the early 17th century until the American Revolution using an analytical narrative and econometric analysis of unique data on franchise restrictions. First, we hold that suffrage changes reflected labour market dynamics. Indeed, Virginia's liberal institutions initially served to attract indentured servants from England needed in the labour-intensive tobacco farming but deteriorated once worker demand subsided and planters replaced white workers with slaves. Second, we argue that Virginia's suffrage was also the result of political bargaining influenced by shifting societal coalitions. We show that new politically influential coalitions of freemen and then of small and large slave-holding farmers emerged in the second half of the 17th and early 18th centuries, respectively. These coalitions were instrumental in reversing the earlier democratic institutions. Our main contribution stems from integrating the labour markets and bargaining/coalitions arguments, thus proving a novel theoretical and empirical explanation for institutional change.
Keywords: D02; N31; N41; P16; 330; democracy; suffrage; colonialism; bargaining; coalitions; Virginia